Binatang dalam Sesenggak Sasak: Kajian Etnolinguistik - Baiq Rismarini Nursaly; Titin Ernawati (SeBaSa)
Sesenggaq in the culture of the Sasak tribe are everyday expressions used. In Indonesian language terms sesenggaqis same as proverbs. The proverb itself in the Main Indonesian Dictionary is explained as; groups of words or sentences that have a fixed structure, impose specific intentions and are short, compact expressions or sentences, containing comparisons, parables, advice, principles of life or rules of behavior. This paper reveals about the use of "animals" in sesenggaq Sasak, why is that, what is the meaning and function. This is due to the fact that there are quite a number of sesenggaq Sasak that use animals in their expressions.This study used a qualitative descriptive method with researchers as the main data source, because they are native speakers of the language studied. This research is explored using an ethnolinguistics perspective which  focuses on the relationship between language and the views of its speakers.